1996
DOI: 10.1037/0022-0663.88.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the school psychological environment and early adolescents' psychological and behavioral functioning in school: The mediating role of goals and belonging.

Abstract: In a sample of 296 8th-grade middle school students, the authors examined the role of personal achievement goals and feelings of school belonging in mediating the relation between perceptions of the school psychological environment and school-related beliefs, affect, and achievement. Sequential regression analyses indicated that perceiving a task goal structure in middle school was positively related to academic self-efficacy and that this relation was mediated through personal task goals. Perceiving an abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
699
5
59

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,037 publications
(831 citation statements)
references
References 60 publications
68
699
5
59
Order By: Relevance
“…In addition, researchers have found that particular learning environments shape students' own personal goal orientations (Kaplan & Maehr, 1999;Nolen & Haladyna, 1990;Roeser, Midgley, & Urdan, 1996). Thus, it would be fruitful to investigate whether classrooms with a mastery-focused goal structure foster transformative experiences and whether this, in turn, facilitates students' conceptual understanding in science.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have found that particular learning environments shape students' own personal goal orientations (Kaplan & Maehr, 1999;Nolen & Haladyna, 1990;Roeser, Midgley, & Urdan, 1996). Thus, it would be fruitful to investigate whether classrooms with a mastery-focused goal structure foster transformative experiences and whether this, in turn, facilitates students' conceptual understanding in science.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the scale's validity and reliability in education settings has been provided through previous research (see Goodenow, 1993). Modified and shortened versions of this scale have been used in subsequent education research and these adapted scales have also demonstrated acceptable reliability (i.e., coefficient alphas > .70) (Anderman, 1999;Anderman & Anderman, 1999;Roeser et al, 1996). Due to these modifications, there are now several versions of the original scale.…”
Section: Social Motivational Orientations Scale For Sport (Smoss)mentioning
confidence: 99%
“…Students who reported a greater sense of belonging were also less likely to be absent or tardy, and more likely to hold higher expectations of school success. Roeser, Midgley, and Urdan (1996) found that 8th grade students with higher perceived belonging also reported a greater sense of academic self-efficacy and positive affect toward school. Similarly, Anderman (1999) also found that 5th and 6th graders reporting higher school belonging also had greater positive affect and lower negative affect toward school.…”
mentioning
confidence: 99%
“…Thus, from the perspective of school belonging and psychological adjustment (Goodenow and Grady, 1993;Roeser et al, 1996;Voekl, 1996), perceptions of ethnic or racial barriers in peer interactions and teaching practices may interfere with the school adjustment of minority students. Accordingly, students who experience ethnic discrimination in class are more prone to resist schoolwork.…”
Section: Perceived Opportunities: the Attitude-achievement Paradoxmentioning
confidence: 99%